Violations of the motor function of the upper digestive tract in children with vegetative dysfunction - Yu.V. Karulina (Zaslavsky O.Yu., 2020)
We conducted a comprehensive clinical, laboratory and instrumental examination of 109 children aged 6-16 years with vegetative dysfunction and digestive complaints. The symptoms of diseases were studied taking into account complaints and anamnestic data, results of an objective examination, general clinical study of blood and urine, biochemical blood test, study of feces for helminth eggs, electrocardiography data, consultations of medical specialists, and ultrasound examination of the abdominal organs. The state of the mucous membrane of the stomach and duodenum and the presence of motor-evacuation disorders in the form of reflux were evaluated according to fibroesophagogastroduodenoscopy. The study of the evacuation function of the stomach was carried out by means of ultrasound examination using the filling method. All children underwent a study of the vegetative regulation of heart rate using cardiac rhythmography. Diagnosis of the levels of situational (reactive) and personality anxiety was carried out using the Spielberger test. A group of children with vegetative dysfunction syndrome and motor disorders of the upper digestive tract was identified. The clinical manifestations, risk factors for the occurrence, types of disorders of the motor function of the upper digestive tract in the autonomic dysfunction syndrome in children were studied, and the relationship between these disorders and H.pylori was determined. All examined children were divided into 2 groups. The main group consisted of 87 children with vegetative dysfunction syndrome and impaired motor function of the upper digestive tract, and the comparison group - 22 children with autonomic dysfunction syndrome with normal motor function of the upper digestive tract. For the purpose of treatment, children of the main group were divided into groups depending on the type of disorders of the motor function of the upper digestive canal: group I had accelerated motor function of the upper digestive tract and group II of patients had a slowdown of this function. The course of treatment for patients of both groups lasted 30 days. The effectiveness of the treatment for vegetative dysfunction syndrome has been proven, taking into account the type of motor disorders of the upper digestive tract.